Local Development Planning Process: A Policy-Level Analysis in Nepal - Sapkota, Bhaba Datta; Malakar, Indra Mali (Journal of Population and Development, 2021)
This study aims at assessing the process and practice of local development planning in Nepal under federal system, with the bid of analyzing the local government operation act, 2074 and local level plan formulation direction, 2075. Using the primary and secondary sources of data, the study embarks on the local development planning process under federal system of Nepal while employing a descriptive research design. Nepal has not experienced long empirical experiences on local development planning exercised under federal democratic republic and it is a totally new practice. The study argues that the local government operation Act, enacted in 2074, conceived the decentralized planning process starting from the settlement level moving up through the local government to the national level and under this all local bodies are required to prepare short, medium and long term, periodic and strategic plans. It concludes that the long term vision of 15th plan of Nepal with "Prosperous Nepal, Happy Nepali" is the foundation for upgrading high income countries by transforming Nepal into socialist oriented public welfare with a rich economy social justice and peaceful living considering local development plan as yardstick and pivot for national long term vision.